A nutritional strategy to promote gilthead seabream performance under low temperatures - Teodósio, Rita (2021)
Gilthead seabream (Sparus aurata) is vulnerable to low water temperature, which may occur in the Southern Europe and Mediterranean region during Winter. Fish are poikilothermic animals, therefore feed intake, digestion, metabolism and ultimately growth are affected by water temperature. This study aimed to evaluate growth performance, feed utilisation, nutrient apparent digestibility, and nitrogen losses to the environment in gilthead seabream juveniles reared under low temperature (similar to 13 degrees C). Three isolipid and isoenergetic diets were formulated: a diet similar to a commercial feed (COM) that contained 44% crude protein and 27.5% fishmeal, and two experimental diets with a lower protein content of 42% (ECO and ECOSup). In both ECO diets fishmeal inclusion was reduced (10% in ECO and 7.5% in ECOSup diet) and 15% poultry meal was included. Additionally, the ECOSup diet was supplemented with a mix of feed additives intended to promote fish growth performance and feed intake. The ECO diets presented lower production costs than the COM diet, whilst incorporating more sustainable ingredients. Gilthead seabream juveniles (+/- 154.5 g initial body weight) were randomly assigned to triplicate tanks and fed the diets for 84 days. Fish fed the ECOSup diet attained a similar final body weight than fish fed the COM diet, significantly higher than fish fed the ECO diet. ECOSup fed fish presented significantly higher hepatosomatic index than COM fed fish, most likely due to higher hepatic glycogen reserves. The viscerosomatic index of ECOSup fed fish were significantly lower compared to COM fed fish, which is a positive achievement from a consumer's point of view. ECOSup diet exhibited similar nutrient digestibility than the COM diet. Moreover, feeding fish with the ECO diets resulted in lower faecal nitrogen losses when compared to COM fed fish. The results suggest that feeding gilthead seabream with an eco-friendly diet with a mix of feed additives such as the ECOSup diet, promoted growth and minimised nitrogen losses to the environment. Nutritional strategies that ultimately promote feed intake and diet utilisation are valuable tools that may help conditioning fish to sustain growth even under low temperatures.